IFRS adoption and foreign direct investment in Sub-Saharan African countries: Does the levels of Adoption Matter? - Fentaw Leykun Fisseha (Cogent Business & Management, 2023)
This study makes an effort to determine how international financial reporting standards (IFRS) adoption levels affect net FDI inflows to sub-Saharan African (SSA) countries using a panel data spans from 2005 to 2020. The results of the two-step system's generalized methods of moments (GMM) estimation reveal that while both partial and full adoption is found to be insignificant, the sign is negative for full IFRS adoption. However, a statistically significant and positive effect of the interaction between institutional attributes and full IFRS adoption has been discovered. Among other factors controlled, the most significant influencing FDI flows to Africa are found to be infrastructure, trade openness, and human capital. The empirical result is used to derive some policy implications.
Keywords: M21; M41; M42; 650; Africa; IFRS adoption; institutional quality; net FDI inflows; system GMM